2022
DOI: 10.1186/s12991-022-00385-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-related perceived stress and social support on generalized anxiety and major depressive disorders: moderating effects of pre-pandemic mental disorders

Abstract: Background We assessed the moderating effect of pre-pandemic mental disorders on the association of COVID-related perceived stress and social support with mental health. Methods A nationally representative sample of 3500 Spanish adults was interviewed in June 2020 (mean age 49.25 years, ± 15.64; 51.50% females). Mental health included Generalized Anxiety Disorders (GAD; GAD-7, cut-off point of ≥ 10), Major Depressive Disorders (MDD; PHQ-8, cut-off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…This finding is in line with previous longitudinal research [ 51 ] and suggests that for recently postpartum women who met the criteria for GAD, the presence of social support did not significantly reduce the impact of anxiety on MDD. Moreover, research has shown that individuals with pre-pandemic mental health disorders experienced little benefit from high levels of social support regarding GAD symptomology [ 52 ]. We did not assess timing of social support which might be important in predicting mental health status among postpartum women [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with previous longitudinal research [ 51 ] and suggests that for recently postpartum women who met the criteria for GAD, the presence of social support did not significantly reduce the impact of anxiety on MDD. Moreover, research has shown that individuals with pre-pandemic mental health disorders experienced little benefit from high levels of social support regarding GAD symptomology [ 52 ]. We did not assess timing of social support which might be important in predicting mental health status among postpartum women [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The factors impacting young people during the pandemic could be grouped in three main areas: i) relationships, ii) lifestyle and health and iii) functionality and economic impact. With respect to relationships, a study with adults in Spain showed that higher levels of social support decreased the probability of having anxiety disorders during the pandemic [25] . The social and mobility restrictions during the early phase of the pandemic represent complex interventions with no homogeneous effect in young people, but with a particular negative effect in their mental health and their relationship with peers.…”
Section: Discussionmentioning
confidence: 99%
“…These epidemiological studies underscore the positive effects of social support on anxiety disorders. Similarly, during the special period of COVID-19’s outbreak, in a cross-sectional survey of 3500 Spanish adults, it was found that for those without pre-pandemic mental disorders, higher levels of social support decreased the odds of GAD-7[ 26 ]. During the COVID-19 pandemic in Turkey, it was also found that anxiety levels decreased significantly when perceived social support increased[ 4 ].…”
Section: Discussionmentioning
confidence: 99%